Smart Trash Bin Berbasis IoT dengan Notifikasi Real-Time Melalui Telegram untuk Optimalisasi Kebersihan Sekolah - Dendy Kurniawan (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
This article discusses the design of a smart trash bin system based on a microcontroller that can provide real-time notifications via the Telegram application when the trash volume reaches its maximum capacity or when unpleasant odors are detected. The system is designed to enhance the efficiency of waste management in an elementary school environment in Central Java, Indonesia. The developed device utilizes two ultrasonic sensors to detect object proximity and trash volume, as well as an MQ4 sensor to identify methane gas as an odor indicator. The NodeMCU serves as the central controller and network interface for sending notifications to Telegram. Testing results demonstrate that the system effectively detects the trash bin's condition and delivers timely and automated notifications to cleaning personnel. This innovation is expected to serve as a practical and effective solution in supporting a cleaner and healthier school environment.